Innovation and change in Japanese management - Haghirian, Parissa, 1970- (Palgrave Macmillan, 2010)
"This book shows which transformation processes and changes can be observed in Japanese companies in reaction to the economic challenges of the past decade. The book presents new research results and investigates the variety of changes that Japanese corporations and managers have experienced in recent years"--Vydavatelská anotace